The Influence of Product Quality, Price, and Brand Image on Consumer Purchase Decisions on Shopee - Rosminah Hayati Nasution; Elvina Elvina; Elida Florentina Sinaga Simanjorang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of product quality, price, and brand image on consumer purchase decisions on Shopee. The independent variables in this study are product quality, price, and brand image, while the dependent variable is the purchase decision. This study uses a quantitative approach with a survey method. The sampling technique used purposive sampling with a total of 96 respondents who had made purchases at Shopee. Data were collected through questionnaire deployment and analyzed using multiple linear regression. The results of the study show that partially product quality, price, and brand image have a positive and significant effect on purchase decisions. Simultaneously, these three variables also have a significant effect on consumer purchase decisions. Product quality variables and brand image have a more dominant influence than price in driving purchase decisions. These findings show that improving product quality, competitive pricing, and building a strong brand image are important strategies in improving consumer purchasing decisions in the marketplace.